(untitled) (Clinics, 2012)
OBJECTIVES: The consequences of breast hypertrophy have been described based on the alteration of body mass distribution, leading to an impact on psychological and physical aspects. The principles of motor control suggest that breast hypertrophy can lead to sensorimotor alterations and the impairment of body balance due to postural misalignment. The aim of this study is to evaluate the postural control of women with breast hypertrophy under different sensory information conditions. METHOD: This cross-sectional study included 14 women with breast hypertrophy and 14 without breast hypertrophy, and the mean ages of the groups were 39 ±15 years and 39±16 years, respectively. A force platform was used to assess the sensory systems that contribute to postural control: somatosensory, visual and vestibular. Four postural conditions were sequentially tested: eyes open and fixed platform, eyes closed and fixed platform, eyes open and mobile platform, and eyes closed and mobile platform. The data were processed, and variables related to the center of pressure were analyzed for each condition. The Kruskal-Wallis test was used to compare the conditions between the groups for the area of center of pressure displacement and the velocity of center of pressure displacement in the anterior-posterior and medial-lateral directions. The alpha level error was set at 0.05. RESULTS: Women with breast hypertrophy presented an area that was significantly higher for three out of four conditions and a higher velocity of center of pressure displacement in the anterior-posterior direction under two conditions: eyes open and mobile platform and eyes closed and mobile platform. CONCLUSIONS: Women with breast hypertrophy have altered postural control, which was demonstrated by the higher area and velocity of center of pressure displacement.